Masticatory Dysfunction by Extensive Tooth Loss as a Risk Factor for Cognitive Deficit: A Systematic Review and Meta-Analysis - Alvarenga, María Olimpia Paz; Ferreira, Railson de Oliveira; Magno, Marcela Baraúna; Fagundes, Nathalia Carolina Fernandes; Maia, Lucianne Cople; Lima, Rafael Rodrigues (Frontiers in Physiology, 2019)
Background: An amount of cognition decline is normal with aging; however, intrinsic and extrinsic risk factors may exacerbate it, affecting social and occupational tasks. Masticatory dysfunction (MD), as a general term, refers to an impairment in the masticatory function triggered by a structural factor, such as tooth loss; functional factors, such as weaker bite force or a poorer masticatory performance; or both factors. MD acting as a source of chronic stress, promotes functional and morphological changes on the hippocampus, a brain area crucial for learning and memory abilities. This study aimed to synthesize evidence on the association between MD and cognitive deficit (CD), and demonstrate whether might be adequately considered as a risk factor. Methods: Observational studies were screened in seven online databases; the search strategy (PECO) was focused in observational studies with humans as a population (P), presenting groups exposed (E) and non-exposed (C) to tooth loss, in which cognition parameters were measured and compared between groups (O). The final selection included only those studies comparing the effect in cognition between subjects having ≥20 remaining teeth and <20 remaining teeth, considering the latter as a structural factor triggering MD by the literature. Searching and data extraction were conducted following PRISMA guidelines. Qualitative and risk of bias evaluations were performed. The meta-analysis (MA) was constructed including the odds ratio (OR) and its 95% confidence interval (CI) comparing two groups—with/without MD. The level of evidence was rated by Grading Recommendations Assessment, Development and Evaluation (GRADE) approach. Results: In total, 5666 citations were identified, 14 accomplished our eligibility criteria, and nine were include in the MA. The MA demonstrates that individuals with MD had 46% higher chance to presented CD (OR 2.24 [1.73, 2.90], p<0.00001, I2= 46%). The level of evidence was rated as low by GRADE. Conclusion: Despite the low certainty in evidence, according to our MA, MD is positively associated with increased risk of CD. However, more studies including other factors underlying MD and similar measurements should be conducted to obtain a strong estimate of the risk.